Is There a Conflict in Employment? Integrating Highly Educated Ukrainian Immigrant Women into the Czech Labor Market - Svyrydova, Mariia (International Journal of Economics and Financial Issues, 2025)
The migration and integration of highly educated Ukrainian women immigrants into the Czech labor market is a serious problem in our increasingly global society. Exploring the influence of active labor market policies (ALMPs) on their integration uncovers both possibilities and challenges, emphasizing the need to understand how government actions may help or impede their professional development. The decision-making processes of these Ukrainian immigrant women will be investigated in this study, with an emphasis on the ways in which ALMPs impact their work integration and migration experiences. Using expert analysis and qualitative interviews, this study explores the institutional and personal dimensions of immigrant women’s integration experiences, shedding light on the systemic challenges and challenges they encounter. The findings indicate that, despite existing integration efforts through ALMPs, significant challenges persist, such as bureaucratic inefficiencies and fragmented support services. These problems can delay access to crucial resources, resulting in underemployment and job mismatches. This study emphasizes the urgent need for a more coordinated policy approach to better support the distinct decision-making processes of highly educated migrant women, ultimately fostering improved outcomes in labor market integration.